Early rabbinic writings - Maccoby, Hyam 1924-2004 (Cambridge commentaries on writings of the Jewish and Christian world, 200 BC to AD 200, 1988)
Rabbinic texts are often cited in New Testament and Old Testament studies, but hitherto there has been no easy way for a student to grasp the scope and variety of the relevant rabbinic writings. This book introduces the student to the full range of the early rabbinic writings, with a thorough introduction and notes, so that both a bird's eye view of the literature as well as close aquaintance with typical and important texts can be obtained. This will enable the reader to embark on further study with a clearer orientation. The book also aims to correct many mistaken views about rabbinic Judaism arising from outdated conceptions of the relation between Christianity and Judaism